EVALUASI PELAKSANAAN PROGRAM GERAKAN LITERASI SEKOLAH DI SEKOLAH DASAR NEGERI - Sitti Roskina Mas; Noval K. Putra Daud; Novianty Djafri (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2019)
Abstract: This research aimed to determine: (1) the context of school literacy movement programs implementation, (2) the input of school literacy movement programs implementation,  (3) the process of school literacy movement programs implementation,  and (4) the product obtained from school literacy movement programs implementation in all of public elementary schools in subdistrict of Paguat. The design of this study was an evaluation study using evaluation model of Process and Product Input Context. (PPIC). The technique of data collection used  questionnaire and interview. The research results showed that: (1) the context of school literacy movement programs implementation was in good category, (2) the input of school literacy movement programs implementation was in good category, (3) the process of school literacy movement programs implementation was in good category, and (4) the product obtained from school literacy movement programs implementation was in good category. It can be concluded that the evaluation of the school literacy movement programs implementation in all of public elementary schools in subdistrict of Paguat have been carried out properly in terms of the implementation of the activities from the habit stage to the learning stages that have been carried out in accordance with the guidelines of school literacy movement implementation. Abstrak: Penelitian ini bertujuan untuk mengetahui: (1) konteks pelaksanaan program gerakan literasi sekolah, (2) input pelaksanaan program gerakan literasi sekolah,  (3) proses pelaksanaan program gerakan literasi sekolah,  dan (4) produk pelaksanaan program gerakan literasi sekolah di SD Negeri se Kecamatan Paguat. Desain penelitian ini bersifat studi evaluasi dengan menggunakan model evaluasi Conteks Input Proses, dan Produk (CIPP). Teknik pengumpulan data yang digunakan  adalah kuesioner, dan wawancara. Hasil penelitian menunjukan bahwa: (1) konteks dalam pelaksanaan program gerakan literasi sekolah berada pada kategori baik, (2) input dalam pelaksanaan program gerakan literasi sekolah berada pada kategori baik, (3) proses dalam pelaksanaan program gerakan literasi sekolah berada pada kategori baik, dan (4) produk dalam pelaksanaan program gerakan literasi sekolah berada pada kategori baik. Kesimpulan dari hasil penelitian bahwa evaluasi pelaksanaan program gerakan literasi sekolah se Kecamatan Paguat sudah dilaksanakan dengan baik, dilihat dari segi pelaksanaan kegiatan dari tahap pembiasaan sampai dengan tahap pembelajaran telah dilakukan sesuai pedoman pelaksanaan gerakan literasi sekolah.